Using Task Analysis to Support Inclusion and Assessment in the Classroom. (July 2022) - McConomy, M. Addie; Root, Jenny; Wade, Taryn
Task analysis is an evidence-based practice that promotes independence and instruction in inclusive settings. Although task analysis has an extensive history in the field of special education, recent research extends the application to both teachers and students, a pro-active approach, and promotes self-monitoring. When students with extensive support needs are provided tools to self-monitor and self-prompt their academic independence increases. This article provides guidance for practitioners as they develop task analysis to support teachers and students during instruction and assessment within an inclusive classroom setting. Recent research to support the value of using task analysis as an educational tool to promote independence and mastery of academic and social instructional goals is reviewed. Readers will also gain practical skills for developing, designing and revising task analysis for individual students, small groups, whole class and teacher use.